Farmers’ Attitude Towards e-Agriculture in Bangladesh (Indian Journal of Extension Education, 2016)
e-Agriculture is being the utmost desire for the sustainable development of worldover. The research was designed to assess farmers’ attitude towards e-Agriculture. The methodology of this study is an integration of quantitative and qualitative methods based on data collection in Bhatbour Block of Dhighi union under Sadar Upazila of Minikganj District. Data were collected from 133 e-Agriculture users. Descriptive statistics, multiple regression (B) were used for analysis. 73.7 percent of the respondents had moderately favorable attitude, 06 percent had low favorable attitude and 20.3 percent had high favorable attitude towards e-Agriculture. Variables such as effective farm size, annual household income, farming experience, participation in training, knowledge on e-Agriculture, organizational participation and cosmopoliteness had significant contribution on farmers’ attitude towards e-Agriculture and these variables contributed total 61.9 percent in farmers’ attitude towards e-Agriculture. Hence, it is high time prepare the farmers to use these e Agriculture tools for their wellbeing through proper educational activities and to popularize this service, government should implement integrated marketing communication using the popular print and electronic media so that more and more people get aware of this service.